2009
DOI: 10.1055/s-0028-1087919
|View full text |Cite
|
Sign up to set email alerts
|

Thieme Chemistry Journal Awardees - Where are They Now? A General One-Step Synthesis of Alkynes from Enolisable Carbonyl Compounds

Abstract: Terminal and internal acetylenes were obtained in good to excellent isolated yields from carbonyl compounds by converting the carbonyl functionality into the enol nonaflate intermediate followed by elimination to give the C-C triple bond. The one-pot transformations were uniformly induced by phosphazene bases combined with mildly electrophilic nonafluorobutane-1-sulfonyl fluoride. The method is the most general among those reported to date as it applies to both acyclic ketones and aldehydes. Only moderate kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 3 publications
0
16
0
2
Order By: Relevance
“…This transformation was accomplished smoothly in two steps by initial conversion to the aldehyde ( 16 – 20 R/S ) through catalytic hydrogenation followed by application of an underutilized direct aldehyde dehydration reaction. 29 Exposure of our highly functionalized aldehydes to nonaflyl fluoride and a strong phosphazane base resulted in a smooth conversion to the terminal alkynes ( 21 – 25 R/S ) with only trace amounts of allene being observed. Importantly, determination of the enantiomeric excess for the derivatives revealed that no epimerization of the propargylic methyl group had taken place under the strongly basic conditions of the reactions.…”
Section: Resultsmentioning
confidence: 89%
“…This transformation was accomplished smoothly in two steps by initial conversion to the aldehyde ( 16 – 20 R/S ) through catalytic hydrogenation followed by application of an underutilized direct aldehyde dehydration reaction. 29 Exposure of our highly functionalized aldehydes to nonaflyl fluoride and a strong phosphazane base resulted in a smooth conversion to the terminal alkynes ( 21 – 25 R/S ) with only trace amounts of allene being observed. Importantly, determination of the enantiomeric excess for the derivatives revealed that no epimerization of the propargylic methyl group had taken place under the strongly basic conditions of the reactions.…”
Section: Resultsmentioning
confidence: 89%
“…2). The dehydration of citronellal in one step and 78% yield is precedented using BTPP (tert-butylimino-tri(pyrrolidino)phosphorane) and NfF (nonafluorobutanesulfonyl fluoride) 23 . However, BTPP is prepared from tert-butyl azide, which slowly eliminates hydrazoic acid and is therefore a safety hazard.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the above results, we decided to apply the methodology to the tetracyclic alkynyl derivative 21 , which was prepared in 50 % overall yield from the advanced intermediate 9 in two steps: acid hydrolysis of the acetal function and subsequent reaction of the resulting somewhat unstable aldehyde with a phosphozene base in the presence of nonafluorobutane‐1‐sulfonyl fluoride (NfF) . Unfortunately, the n BuLi‐promoted coupling of 21 with the non‐activated iodide 17 under the previously established conditions occurred with abundant decomposition, affording the desired dienyne 22 in negligible yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In view of the above results, we decided to apply the methodology to thet etracyclic alkynyl derivative 21,w hichw as prepared in 50 %o verall yield from the advanced intermediate 9 in two steps:a cid hydrolysis of the acetal function and subsequent reactiono ft he resulting somewhat unstable aldehyde with ap hosphozene base in the presence of nonafluorobutane-1-sulfonyl fluoride (NfF). [17] Unfortunately,t he nBuLi-promotedc oupling of 21 with the non-activated iodide 17 under the previously established conditions occurred with abundant decomposition, affording the desired dienyne 22 in negligible yield (Scheme 6). Extensive decomposition, or recovery of the startingm aterial, was also observed in the attempts to induce the coupling from tricyclic alkyne 23,which was preparedf rom 8 by the procedure previously used for 21.T he strong nucleophilic character of nBuLi combined with the presence of a lactam or ester carbonyl group could account for the failure of the above coupling reactions.…”
Section: Studiesonthe Construction Of the Dr Ing Of Madangamine Bmentioning
confidence: 99%